Tirani Kebahagiaan dan Media Sosial: Sebuah Kajian Media dan Politik - Alamsyah, Anggriani (Jurnal Politik Profetik, 2023)
Social media content has taken up a lot of our attention, a lot of time and energy is spent either creating content or just exploring it. This of course does not only have a positive impact on us, on the other side of the pendulum there are ’mines’ ready to blow up anyone who is not aware of the negative effects. This paper attempts to provide an overview of the hidden agendas of social media that are consciously or unconsciously realized by its users, where the hedonic treadmill concept is used as the main analysis knife. This article is qualitative by using impressions on YouTube as the object of writing. Shows that are used as the object of analysis include: 1) Why Social Media Is Toxic for Teen Mental Health | Fault Lines Documentary; 2) Teens, Social Media, and Technology (Full Documentary; 3) The Instagram Effect 2022 Documentary. The author finds that social media has great potential to encourage a continuous search for happiness as evidenced by the acquisition of as many like-view-shares as possible. In addition, the next finding is that social media makes a major contribution to the formation of a negative image of the body and mental disorders that lead to suicide. The ultimate terminal is the utilization of algorithms to generate more profit for social media.